Association between ambient beta particle radioactivity and lower hemoglobin concentrations in a cohort of elderly men. (June 2020) - Vieira, Carolina L.Z.; Garshick, Eric; Alvares, Danilo; Schwartz, Joel; Huang, Shaodan; Vokonas, P.; Gold, Diane R.; Koutrakis, Petros
Highlights: Exposures to low-dose environmental radiation emitted from particulate matter is associated with a reduction in hemoglobin levels in elderly men. The effects of air pollutants on hemoglobin levels may depend on their physicochemical properties. Environmental ionizing radiation released from particulate matter may contribute to the development of anemia. Abstract: Although ionizing radiation is known to have detrimental effects on red blood cells, the effect of environmental radioactivity associated with ambient particulate matter (PM) is unknown. We hypothesized that exposure to ambient PM-associated beta particle radioactivity (PRβ ) would be associated with a lower hemoglobin concentration. We studied 1.704 participants from the Normative Aging Study (NAS) over 36 years (1981–2017) who lived in Eastern, MA and the surrounding area. Exposures to PRβ was assessed using USEPA's RadNet monitoring network that measures gross beta radiation associated with ambient PM. Mixed effect models with a random intercept adjusting for potential confounders was used, including ambient black carbon (BC) and particulate matter ≤2.5 μm (PM2.5 ) concentrations. Greater cumulative PRβ activities at 7-, 14-, 21- and 28-days before the hemoglobin determination were associated with lower hemoglobin concentrations. The greatest effect was for a 28-day moving average. An IQR of 0.83 × 10 −4  Bq/m 3 of ambient PRβ was associated with a 0.12 g/dL decrease in hemoglobin concentration (95%CI: −0.18 to −0.05). The effects of PRβ were similar when the models were adjusted for ambient BC or PM2.5 . This is the first study to demonstrate an association between environmental ionizing radiation released from particulate matter with a lower hemoglobin concentration, suggesting that ambient radiation may contribute to the development of anemia.